2018
DOI: 10.7456/1080sse/102
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hotel Website Design Quality, Perceived Ease of Use and Perceived Usefulness on Loyalty Intention

Abstract: This study develops and empirically examines a theoretical model to investigate these relationships. 136 usable responses from online survey were analyzed using partial least squares -structural equation modelling (PLS-SEM) approach. The present article contributes to the existing body of knowledge by identifying the influence of website design quality on perceived ease of use, perceived usefulness and loyalty intention among hotel website users. Results indicated that website design quality, perceived ease of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
(14 reference statements)
0
3
1
Order By: Relevance
“…Thus, hypothesis 6 (H6) is not supported. This finding is different from previous studies (Bahari et al, 2018;Khan & Khan, 2020;Wilson et al, 2021), which state that perceived ease of use has a significant effect on loyalty. However, a study found that perceived ease of use has no impact on loyalty to social media users based on Online Brand Community (Potgieter & Naidoo, 2017) The perceived ease of use in conducting transactions using e-commerce, apparently does not necessarily make millennials loyal.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, hypothesis 6 (H6) is not supported. This finding is different from previous studies (Bahari et al, 2018;Khan & Khan, 2020;Wilson et al, 2021), which state that perceived ease of use has a significant effect on loyalty. However, a study found that perceived ease of use has no impact on loyalty to social media users based on Online Brand Community (Potgieter & Naidoo, 2017) The perceived ease of use in conducting transactions using e-commerce, apparently does not necessarily make millennials loyal.…”
Section: Discussioncontrasting
confidence: 99%
“…Wakefield et al (2004) in K. A. [8] stated the technological aspect of a website such as layout, appearance, and navigation. The method used to measure the quality of a website is based on the perception of the end-users [9].…”
Section: Website Design Qualitymentioning
confidence: 99%
“…Mustapha and Obid [35] showed a direct positive relationship between online tax service quality and perceived ease of use. Bahari et al [36] showed a similar result in their hotel website design studies. Li and Shang [37] suggested that e-government service quality affected perceived service value.…”
Section: Hypothesis 31 (H31) Confirmation Has a Positive And Significant Effect On Perceived Value Hypothesis 32 (H32) Confirmation Has Amentioning
confidence: 54%